Dynamic stabilization of formation ﬁnes to enhance oil recovery of a medium permeability sandstone core at reservoir conditions - Agi, Augustine Aja; Radzuan, Junin; Mohd Zaidi, Jaafar; Zulkifli, Abdul Majid; Nor Aishah Saidina, Amin; Akhmal, Sidek; Yakasai, Faruk; Muhammad Abbas Ahmad, Zaini; Azrul Nurfaiz, Mohd Faizal; Gbadamosi, Afeez Olayinka; Sirajo, Lawal; Oseh, Jeffrey Onuoma (Elsevier B.V., 2023)
Fines migration has impacted the efficiency of low salinity water flooding at reservoir condition. However, previous studies on the use of nanoparticles to combat this problem were not done at reservoir condition and the effect of porous media length was neglected. Hence, the objective of this study is to use mesoporous silica (SiO2) nanoparticles (MSNP) to stabilize formation fines to increase oil recovery during low salinity water flooding at reservoir condition. Likewise, effect of porous media length on dynamic retention of fines at high temperature high pressure (HTHP) reservoir condition was investigated. The breakthrough curves of reservoir fines adsorption by mesoporous SiO2 nanofluid (MSNF) were described using the Thomas and Yoon-Nelson models. Subsequently, the effect of reservoir fines stabilization on oil recovery was evaluated using a HTHP core flooding equipment. Also, the formation damage remediation propensity of MSNF was investigated. Finally, the oil recovery mechanism was determined using the sessile drop contact angle method. Experimental results of the dynamic adsorption with coefficient of determination (R2) values in the range of 0.967–0.999 signifies that the reservoir fines adsorption by MSNF were well predicted by Thomas and Yoon-Nelson models. Consequently, MSNF stabilized the reservoir fines by attaching onto their surface rather than on the porous media thereby changing the wettability to water-wet, decreasing the contact angle to 16.1°, 17.1° and 20.7° for kaolinite, illite and montmorillonite, respectively. Subsequently, increasing oil recovery by 22–23% original oil in place. Therefore, the use of MSNF to stabilize formation fines at reservoir condition is proffered.